Kepuasan Konsumen Terhadap Atribut Produk Olahan Pisang (Studi Kasus Cake Banana Foster di Bandar Lampung) - Amanda Hardianti, Dwi; Desfaryani, Rini; Sutarni, Sutarni; Apriyani, Marlinda (Politeknik Negeri Lampung, 2024)
This research aimed to analyze consumer characteristics as well as find out the level of importance of attributes and the level of consumer satisfaction with the performance of the processed product attributes of Banana Foster banana cake. This research used 5 attributes, namely price, taste, texture, packaging, and service. The data analysis methods used were Descriptive, Importance Analysis Performance (IPA) and Customer Satisfaction Index (CSI). The result of the consumer characteristics of Banana Foster Lampung cake showed that the customers were dominated by females and were 19-29 years of age, had the last education of SMA/SMK, had a monthly income of Rp 3,000,000 - Rp 4,500,000 and had private sector jobs. The level of consumer interest in quadrant 1 (main priority) was relatively affordable price, good taste, and fast service. Therefore, these attributes were considered important by consumers while the performance level of the attribute was still low. Attributes that must maintain their superiority or attributes located in quadrant II were price, aroma, and texture. The consumer satisfaction index was at 84.1% satisfaction index and belonged to very satisfied criteria.